Aktivitas Afrodisiak Ekstrak Etanol Daun Tumbuhan Bungkus (Smilax rotundifolia L.) terhadap Fertilitas Tikus Putih Jantan (Rattus norvegicus): The Aphrodisiac Activity of Ethanol Extract of Bungkus Leaf (Smilax rotundifolia L.) on The Fertility of White Male Rats (Rattus norvegicus) - Ayu Wulandari; Recky Patala; Kiki Rizki Handayani; Monica Sandra Makatang (KOVALEN: Jurnal Riset Kimia, 2022)
Aphrodisiac is a substance that can increase stamina, libido (sexual desire), and male fertility. This study aims to determine the secondary metabolites contained in the leaves of the Bungkus plant (Smilax rotundifolia L.), to determine the aphrodisiac activity of the leaf extract of the Bungkus plant on the fertility parameters of male white rats (Rattus norvegicus). This study used an experimental method with a modified post-test randomized controlled group design using 15 male white rats and 30 female white rats which were divided into 3 treatment groups, namely pairing each male rat with 2 female white rats (1 : 2). Each group consisted of 5 male rats and 10 female rats, namely the normal control group (NaCMC 0.5%), the positive control group (X-Gra 51.37 mg/kgBW), the control group the leaf extract test sample of the Bungkus plant (S. rotundifolia L.) with a dose of 200 mg/kgBW. The research data were analyzed using the SPSS 25 statistical test. The results of this study indicate that the leaf extract of the Bungkus plant contains secondary metabolites flavonoids, saponins, alkaloids and tannins. The administration of Bungkus leaf extract at a dose of 200 mg/kgBW showed a difference in the percentage value of the pregnancy index and a significant effect on the fertility index value.